Pattern of money allocation in experimental games supports the stress hypothesis of gender differences in Toxoplasma gondii-induced behavioural changes - Lindová, Jitka; Kubena, Ales A; Sturcová, Hana; Krivohlavá, Romana; Novotná, Martina; Rubesová, Anna; Havlícek, Jan; Kodym, Petr; Flegr, Jaroslav (Folia parasitologica, 2010)
Latent toxoplasmosis has been previously found to cause behavioural and personality changes in humans, which are specific for each gender. Here we tested the stress hypothesis of these gender differences based on the assumption that latent toxoplasmosis causes long-term subliminal stress. In line with this hypothesis, the gender difference will appear specifically in situations with interpersonal context because in contrast to the typical individualistic coping style of men, women have a tendency to express elevated prosocial behaviour under stress. Altogether 295 biology students (29/191 females and 27/104 males infected by T. gondii) played a modified version of the Dictator Game and the Trust Game. As predicted, a gender difference in the effect of latent toxoplasmosis was found for the measure of reciprocal altruism in the Trust Game (p = 0.016), but both genders appeared less generous when infected in the Dictator Game modified to minimize social connotation (p = 0.048).
Keywords: Young Adult; Toxoplasma; Male; experimentální hry; Sex Characteristics; mladý dospělý; toxoplazmóza; mužské pohlaví; pohlavní dimorfismus; Stress, Physiological; Animals; lidé; Toxoplasmosis; ženské pohlaví; Games, Experimental; Humans; zvířata; Female; fyziologický stres